Macrophage polarisation changes within the time between diagnostic biopsy and tumour resection in oral squamous cell carcinomas-an immunohistochemical study - Weber, Manuel; Moebius, P.; Büttner-Herold, M.; Amann, Kerstin Ute; Preidl, Raimund; Neukam, Friedrich Wilhelm; Wehrhan, Falk (British Journal of Cancer, 2015)
The prognosis of solid malignancies has been shown to depend on immunological parameters, such as macrophage polarisation (M1/M2). Recently, it was reported that preoperative oral surgery leads to a worsening of oral squamous cell carcinomas (OSCC) prognosis. Diagnostic incision biopsies are oral surgery procedures that might lead to healing-associated M2 macrophage polarisation with a potential negative influence on tumour biology. No studies have compared macrophage polarisation in OSCC biopsies and tumour specimens.Preoperative diagnostic incision biopsies (n=25) and tumour resection specimens (n=34) of T1/T2 OSCC were processed for immunohistochemistry to detect CD68-, CD11c-, CD163- and MRC1-positive cells. Samples were digitised using whole-slide imaging, and the expression of macrophage markers was quantitatively analysed.Carcinoma tissues obtained during OSCC tumour resections showed a significantly (P<0.05) increased CD163 cell count (M2 macrophages) compared with tissues obtained during preoperative incision biopsies. Additionally, the CD163/CD68 ratio (an indicator of M2 polarisation) was significantly (P<0.05) higher in tumour resection specimens than in biopsies.This study revealed for the first time an increase in M2 polarisation in samples obtained during OSCC tumour resection surgery compared with preoperative incision biopsies. The biopsy-induced tissue trauma might explain the observed shift in macrophage polarisation towards the tumour-promoting M2 type and could lead to accelerated tumour progression.
EVALuna2:24401